Geraldocossus gen. nov. (Lepidoptera, Cossidae) from Mount Cameroon (West Africa) - Yakovlev, Roman V.; Sáfián, Szabolcs (Zootaxa, 2016)
The cossid or the Carpenter Moths (Lepidoptera, Cossidae) include about 1000 species worldwide (van Nieukerken et al., 2011), of which 750 species belong to five subfamilies that occur in the Old World (Yakovlev 2011). The Cossidae are still relatively poorly known from vast areas of the African continent, despite recent reports on the fauna of Malawi (Yakovlev & Murphey 2014), Zimbabwe (Yakovlev & Lenz 2014), and Zambia (Yakovlev 2014). The first results of an ongoing revision of the South African Cossidae have also been published (Mey 2015).